Accuracy of Five Serologic Tests for the Follow up of Strongyloides stercoralis Infection - Buonfrate, Dora (2015)
Background Traditional faecal-based methods have poor sensitivity for the detection of S. stercoralis, therefore are inadequate for post-treatment evaluation of infected patients who should be carefully monitored to exclude the persistence of the infection. In a previous study, we demonstrated high accuracy of five serology tests for the screening and diagnosis of strongyloidiasis. Aim of this study is to evaluate the performance of the same five tests for the follow up of patients infected with S. stercoralis. Methods Retrospective study on anonymized, cryo-preserved samples available at the Centre for Tropical Diseases (Negrar, Verona, Italy). Samples were collected before and from 3 to 12 months after treatment. The samples were tested with two commercially-available ELISA tests (IVD, Bordier), two techniques based on a recombinant antigen (NIE-ELISA and NIE-LIPS) and one in-house IFAT. The results of each test were evaluated both in relation to the results of fecal examination and to those of a composite reference standard (classifying as positive a sample with positive stools and/or at least three positive serology tests). The associations between the independent variables age and time and the dependent variable value of serological test (for all five tests), were analyzed by linear mixed-effects regression model. Results A high proportion of samples demonstrated for each test a seroreversion or a relevant decline (optical density/relative light units halved or decrease of at least two titers for IFAT) at follow up, results confirmed by the linear mixed effects model that showed a trend to seroreversion over time for all tests. In particular, IVD-ELISA (almost 90% samples demonstrated relevant decline) and IFAT (almost 87%) had the best performance. Considering only samples with a complete negativization, NIE-ELISA showed the best performance (72.5% seroreversion). Conclusions Serology is useful for the follow up of patients infected with S. stercoralis and determining test of cure